Patterns of housework performance in the United States before, during, and after the Great Recession - Davis, Shannon N. (Frontiers in Sociology, 2023)
Housework is a key area of research across many academic fields as it represents the intersection of micro- and macro-level gender dynamics. Despite many shifts in both women's and men's economic activities, and men's changing gender beliefs, women remain largely responsible for the management and performance of domestic labor. Given the relationship between paid employment and household work, this research describes patterns of women's and men's housework before, during, and after the Great Recession. Using American Time Use Survey data, I perform latent profile analysis to document the distributions of housework tasks and time for women and men across these three time periods. While women perform the majority of housework across the time frame, women and men converge in their time during the Recession. Further, men's time becomes more varied and more similar to women's Post-Recession. The findings in this research brief highlight the connections between macro-level change and micro-level behavior.